Testing Hardy's nonlocality proof with genuine energy-time entanglement - Vallone, G; Gianani, I; Inostroza, E; Saavedra, C; Lima, G; Cabello, A; Mataloni, P (2011)
We show two experimental realizations of Hardy's ladder test of quantum nonlocality using energy-time correlated photons, following the scheme proposed by Cabello [Phys. Rev. Lett.PRLTAO0031-900710.1103/PhysRevLett.102.040401 102, 040401 (2009)]. Unlike previous energy-time Bell experiments, these tests require precisely tailored nonmaximally entangled states. One of them is equivalent to the two-setting and two-outcome Bell test requiring a minimum detection efficiency. The reported experiments are still affected by the locality and detection loopholes, but are free of the post-selection loophole of previous energy-time and time-bin Bell tests. © 2011 American Physical Society.